2017
DOI: 10.1016/j.ajo.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Outcomes From a Randomized Clinical Trial Comparing Antimetabolites for Intermediate, Posterior, and Panuveitis

Abstract: Purpose To evaluate the changes in quality of life in noninfectious uveitis patients treated with two of the most commonly prescribed antimetabolite treatments. Design Secondary analysis of a multicenter, block-randomized, clinical trial (ClinicalTrials.gov NCT01232920). Methods Eighty patients at Aravind Eye Hospitals in Madurai and Coimbatore, India, with noninfectious intermediate, posterior, or panuveitis were randomized to receive oral methotrexate, 25 mg weekly, or oral mycophenolate mofetil, 1 g twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
(41 reference statements)
2
6
0
1
Order By: Relevance
“…49,50 Prior analyses suggest that visual acuity is associated with poorer quality of life, but consistent with our study, it is a weak to moderate predictor. [49][50][51][52] The low number of predictors associated with PSS-10 scores illustrates the complexity of the concept being evaluated. Psychological stress is a subjective and heterogeneous experience that can be affected by many factors, not all of which can be captured by standardized survey data.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Prior analyses suggest that visual acuity is associated with poorer quality of life, but consistent with our study, it is a weak to moderate predictor. [49][50][51][52] The low number of predictors associated with PSS-10 scores illustrates the complexity of the concept being evaluated. Psychological stress is a subjective and heterogeneous experience that can be affected by many factors, not all of which can be captured by standardized survey data.…”
Section: Discussionmentioning
confidence: 99%
“…Niemeyer et al concluded using IND-VFQ scores, on average, over its 6 months study period (p = 0.0001) [12]. They observed a decreased mental component summary score (p = 0.04) and decreased vitality subscale (p = 0.001), while the SF-36 physical component summary score did not significantly differ throughout the trial.…”
Section: Discussionmentioning
confidence: 96%
“…Niemeyer et al concluded using IND-VFQ scores, on average, over its 6 months study period (p = 0.0001) [13]. They up Study [14].…”
Section: Discussionmentioning
confidence: 98%